Hungarian Contributions on American History and Culture, 2020-2022 - Kovács, Ágnes Zsófia (AMERICANA E-journal of American Studies in Hungary, 2023)
The compilation below surveys American Studies scholarship published in Hungary in 2020, 2021 and 2022. Ágnes Zsófia Kovács compiled and organized the material.